Automatic Essay Grading System for Japanese Language Examination Using Winnowing Algorithm - Agung Putri Ratna, Anak; Lalita Luhurkinanti, Dyah; Ibrahim, Ihsan; Husna, Diyanatul; Dewi Purnamasari, Prima (2018 International Seminar on Application for Technology of Information and Communication, 2018)
This paper explained a research that was conducted to find the best methodology for automatic essay grading. The Winnowing method was used in this paper with specific application for Japanese language exam. With Japanese language input, romanization was implemented to change the input that were in hiragana, katakana, or kanji into romaji. After the system was developed, it still needed to find the best parameters with the highest accuracy or closer even similar to the results from human rater. From testing the short essay Japanese language exam answers with 100% of score from human rater, several testing show that the best parameter for this system is with n=2, w=2, and p=2 and the average accuracy of total score gathered for all students is 86.86%. Since the average accuracy is above 80%, it could be concluded that winnowing algorithm is suitable for Japanese language examination term.